The first hall of fame : a study of the statues in the Forum Augustum - Geiger, Joseph. (Mnemosyne, Supplements, 2008)
Although both national sites of commemoration and Halls of Fame for a variety of human endeavours are widespread, little thought was given to the fact that the statues in the Forum Augustum were the first assemblage of this kind. This book identifies the Greek and Roman backgrounds to and influences on Augustus' decision as well as his probable motives for setting up these statues. The central chapters deal with the structure of the Forum and its statues, and provide a detailed analysis of the list of men (and women) known to have been included and the criteria for inclusion. Finally the additions to the heroes between Augustus and Trajan and the later impact of this Gallery of Heroes are discussed.